PENDIDIKAN ABAD 21 UNTUK ANAK USIA DINI: MEMBANGUN KARAKTER, TEKNOLOGI, DAN LITERASI SEJAK DINI - Asmayawati, Asmayawati; Masliati, Tati (Jurnal Anak Bangsa, 2025)
21st century education prioritizes the development of relevant skills to face global challenges, such as creativity, critical thinking, collaboration, and digital literacy. In early childhood, it is important to instill strong character values, technology skills, and literacy from an early age. This study aims to analyze the importance of 21st century education in early childhood with a focus on character development, technology introduction, and literacy. The research methods used are literature studies and observations in several PAUD institutions in Indonesia. The results of the study indicate that the integration of technology in the learning process, character development, and literacy in early childhood is very important to equip them to face future challenges. In conclusion, 21st century education in early childhood needs to be directed at the development of holistic skills involving moral, intellectual, and technological aspects.